Gestión financiera de las cuentas de ingresos y gastos del Gobierno Autónomo Descentralizado Rural de la Parroquia Balsapamba perteneciente al cantón San Miguel en la provincia de Bolívar en el periodo 2023. - Campos Bósquez, Jefferson Alexander (2024)
The case study focused on the financial management of the Decentralized Autonomous Government GAD of the Balsapamba parish during the period 2023 displays a detailed analysis of how public resources are administered in a rural context, highlighting the relevance of efficient and transparent management in accordance with the constitutional and legal guidelines of Ecuador. The justification of the study lies in the prevailing need to optimize public resources, guaranteeing their adequate allocation and use in favor of community development and improvement of the quality of life of the inhabitants, given the evident deficiencies in the control and execution of the budget observed in previous periods. This methodological approach allowed us to unravel the dynamics of financing, allocation and management of resources with precision, facilitating the understanding of the financial structure of the GAD and its impact on the parish. The results obtained reveal a financial management that, despite being oriented towards social development and support for rural parish councils, shows deficiencies in the effective collection of income and in the execution of investment projects, reflecting an underutilization of available resources. and a significant gap between what was budgeted and what was executed.